An Anatomical Study of the Tibia in the North Indian Population - Tiwari, A; Mahendru, A; Priya, A (International Journal of Human Anatomy, 2019)
Introduction The human tibia is a complex anatomical unit and the knowledge of its morphometric values is important in Forensic, Anatomic and Radiological cases in order to identify unknown bodies and stature. Objective It was to analyze the tibia, its morphometry, side difference and to investigate the position of nutrient foramina in tibia. Methods In this study, 60 adult human tibias (30 right and 30 left) were obtained from the Department of Anatomy SMSR SHARDA UNIVERSITY. In the study a total of two parameters i.e. Cross Section Index in the middle and Cnemicus Index of the bones were obtained and evaluated by using two instruments- a Measuring Tape and a Vernier Calipers. All the bones were dry and showed normal anatomical features. Results The mean Cross Section Index in the middle was calculated as 80.42 ± 11.33 on the right side and 78.15± 12.78 on the left side; and the Cnemicus index was 78.40 ± 13.19 on the right side and 70.84 ± 11.38 on the left side Conclusion The two parameters in the North Indian population were compared with other populations. The values were found to be almost comparable however there were subtle differences between different populations. The position of nutrient foramen was also assessed. This knowledge will thus help further researchers and orthopedic surgeons in various procedures like joint replacement therapy, fracture repair, bone grafts and vascularized bone microsurgery as well as in medico‐legal cases.
Keywords: Tibia; Dimensions; Cross-Sectional Index; Cnemicus Index